Wild wings - Lewis, Gill.; Onoda, Yuta (New York : Atheneum Books for Young Readers, 2011)
Callum becomes friends with Iona, a practically feral classmate who has discovered an osprey, thought to be gone from Scotland, on Callum's family farm, and they eventually share the secret with others, including Jeneba who encounters the same bird at her home in Gambia.
"A Junior Library Guild selection"--Jkt. flap.
Ages 8-12.
Keywords: Friendship -- Fiction; Osprey -- Fiction; Rare birds -- Fiction; Birds -- Fiction; Farm life -- Scotland -- Fiction; Scotland -- Fiction; Gambia -- Fiction